Digital Smile Design and mock-up technique in esthetic crown lengthening: 2-year follow-up of six cases - Pires, Luana Carla; Leandrin, Thais Piragine [UNESP]; Aroni, Mauricio Andres Tinajero; de Oliveira, Guilherme José Pimentel Lopes; Barbeiro, Roberto Henrique [UNESP]; Verzola, Mario Henrique; Cirelli, Joni Augusto [UNESP]; Pigossi, Suzane Cristina (My University, 2022)
The present case series aimed to evaluate the use of a Digital Smile Design (DSD) and mock-up technique for esthetic crown lengthening (ECL) surgery in six clinical cases with a 2-year follow-up. Six nonsmoker patients (five females, one male; aged 22 to 32 years), periodontally and systemically healthy, with inadequate tooth width/height ratio proportions associated with a gingival misalignment in the anterior maxilla were included. The DSDs were created using PowerPoint for all patients to evaluate gingival level and tooth form/contour. A wax-up and mock-up were created based on the DSD measurements. ECL surgeries were performed in all cases using the mock-up technique to determine the final gingival margin position and the amount of bone resection needed. A mock-up to bone crest distance of 3 mm was obtained in all cases. Using patient photographs, comparisons were made between the dental crown length (DCL) measurements obtained before the surgical procedure (baseline; T0), on the DSD template immediately postoperatively (IPO; T1), and at the 2-year follow-up (T2). A DCL augmentation of 1.16 ± 0.68 mm was obtained at T1, with an augmentation of 1.03 ± 0.73 mm at T2. Moreover, a minimal difference of 0.34 ± 0.74 mm between the DCL planned in the DSD template and the DCL obtained IPO was observed. In conclusion, the ECL procedure based on the DSD concept and mock-up technique proposed in this cases series was a predictable protocol for smile disharmony treatment in all the patients.